Perfil sociodemográfico e motivos do espectador de basquetebol (2023)
This study aimed to identify people's motives to attend basketball games and their socio-demographics characteristics. A total of 459 questionnaires were answered within eight play-off matches at the Liga de Clubes de Basquetebol 2008 championship and through a factor analysis it was possible to identify that belonging to city and team, escape, family, knowledge of the game, physical skills, interest in player and drama are the most important motives. The demographics analysis suggests diversity in spectators according to age, gender, education level, household, income, geographical proximity, companion and basketball experience.